Making conservation sustainable under unfavourable conditions: the case of Chimanimani National Reserve, Mozambique. Issue 3 (2nd April 2020) - Virtanen, Pekka
ABSTRACT: Based on a case study from the Chimanimani National Reserve in Mozambique, this article analyses to what extent different types of operational practices can contribute to the sustainability of protected areas in relatively unfavourable external conditions. While current conservation policies highlight community participation and market-based approaches, the same "best practices" are not equally valid under different conditions. Where unfavourable natural conditions, lack of infrastructure, difficult access and political instability limit the potential for upmarket ecotourism, actors should focus on community empowerment, diversification of livelihoods, and building joint conservation ideology, where they have direct influence through operational practices.